The Effectiveness of thought stopping on the level of compliance in taking antihypertension medication in the elderly - Usraleli, Usraleli; Forwaty, Erni; Khusniyati, Nia; Daulay, Wardiyah; Oktariani, Falinda; Putri, Vevi Suryenti (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2025)
Background: It is hypothesised that thought stopping and assertive training represent a behavioural therapy that may assist in overcoming negative thoughts that impede relaxation and, consequently, the reduction of hypertension. It is proposed that medication compliance represents a pivotal factor in the management of blood pressure in patients with hypertension.. Method: The objective of this study was to ascertain the efficacy of thought stopping in enhancing compliance with hypertension treatment. The research design employed was a pretest-posttest group design with a control group. The study employed a pretest-posttest group design with a control group to compare the results of the group that received Thought Stopping treatment (the intervention group) with the group that received Assertive Training Results: The data obtained on the level of compliance with taking anti-hypertensive drugs before and after the intervention revealed that 12.5% of the participants were compliant, while 87.5% were non-compliant. The statistical test results for the variable of thought stopping therapy yielded a p-value of 0.201, indicating that there was no statistically significant difference in the mean systolic blood pressure between the pre- and post-therapy periods at the 5% alpha level. Similarly, the statistical test results for the variable of thought stopping therapy yielded a p-value of 0.093, indicating that there was no statistically significant difference in the mean diastolic blood pressure between the pre- and post-therapy periods at the 5% alpha level. Conclusion: The administration of Thought Stopping Therapy did not result in a statistically significant change in the mean systolic and diastolic blood pressure values between the pre- and post-therapy periods.